Dispersive Fast Magnetosonic Waves and Shock‐Driven Compressible Turbulence in the Inner Heliosheath. Issue 10 (3rd October 2020) - Zieger, Bertalan; Opher, Merav; Tóth, Gábor; Florinski, Vladimir
Abstract: The solar wind in the inner heliosheath beyond the termination shock (TS) is a nonequilibrium collisionless plasma consisting of thermal solar wind ions, suprathermal pickup ions, and electrons. In such multi‐ion plasma, two fast magnetosonic wave modes exist, the low‐frequency fast mode and the high‐frequency fast mode. Both fast modes are dispersive on fluid and ion scales, which results in nonlinear dispersive shock waves. We present high‐resolution three‐fluid simulations of the TS and the inner heliosheath up to a few astronomical units (AU) downstream of the TS. We show that downstream propagating nonlinear fast magnetosonic waves grow until they steepen into shocklets, overturn, and start to propagate backward in the frame of the downstream propagating wave. The counterpropagating nonlinear waves result in 2‐D fast magnetosonic turbulence, which is driven by the ion‐ion hybrid resonance instability. Energy is transferred from small scales to large scales in the inverse cascade range, and enstrophy is transferred from large scales to small scales in the direct cascade range. We validate our three‐fluid simulations with in situ high‐resolution Voyager 2 magnetic field observations in the inner heliosheath. Our simulations reproduce the observed magnetic turbulence spectrum with a spectral slope of −5/3 in frequency domain. However, the fluid‐scale turbulence spectrum is not a Kolmogorov spectrum in wave number domain because Taylor's hypothesis breaks down in the inner heliosheath. The magnetic structure functions of the simulated and observed turbulence follow the Kolmogorov‐Kraichnan scaling, which implies self‐similarity. Key Points: Nonlinear dispersive fast magnetosonic waves produce 2‐D compressible turbulence downstream of the termination shock Taylor's hypothesis breaks down in the subfast magnetosonic solar wind in the inner heliosheath The magnetic turbulence spectrum observed by Voyager 2 in the inner heliosheath is reproduced by self‐consistent three‐fluid MHD simulation